Pengaruh Word of Mouth Marketing dan Pameran terhadap Keputusan Orang Tua Memilih Sekolah - Hartiwi Prabowo; Lily Lily (Bina Nusantara University, 2011)
In decision-making of choosing schools, people recommendation is effected. WOM factor and exhibition twice in a year for ISMILE school is a considered efficient and effective promotional media. The research method is to identify the effect of word of mouth and exhibition towards perception of value proposition and effects of decision-making. Analysis method in this research is validity, reliability, normality test, simple correlation and path analysis. Data gathering technique is questionnaire. The repondents in the research are 100 people, including parents from students in ISMILE school. The expected result from this research is a relationship among variables, significant effects from word of mouth and exhibition at the same time of perception towards value position and significant effects from perception of value proposition towards decision- making. From this research, ISMILE school should hold exhibition and focus to things that will lead to positive word of mouth so it could gain more parents register their children in ISMILE school.